2017
DOI: 10.1177/2057158517713156
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for patient participation: Psychometric evaluation of The 4Ps tool in patients with chronic heart or lung disorders

Abstract: The Patient Preferences for Patient Participation tool (The 4Ps) was developed to aid clinical dialogue and to help patients to 1) depict, 2) prioritise, and 3) evaluate patient participation with 12 pre-set items reiterated in the three sections. An earlier qualitative evaluation of The 4Ps showed promising results. The present study is a psychometric evaluation of The 4Ps in patients with chronic heart or lung disease (n ¼ 108) in primary and outpatient care. Internal scale validity was evaluated using Rasch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…According to the quality of care δ values, the items originating from the subscales respect and integrity and information and knowledge were considered as easier to satisfy and the items originating from the subscales planning and decision making and motivation and encouragement were considered as more difficult to satisfy (Table ). This could be considered, qualitatively and when comparing to other scales, as creating successful hierarchical rulers. Despite some minor misfits and significant item‐trait interaction chi‐square tests ( P < 0.001), the cumulated fit statistics showed that the PPRQ‐17 acceptably satisfies the RMT (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the quality of care δ values, the items originating from the subscales respect and integrity and information and knowledge were considered as easier to satisfy and the items originating from the subscales planning and decision making and motivation and encouragement were considered as more difficult to satisfy (Table ). This could be considered, qualitatively and when comparing to other scales, as creating successful hierarchical rulers. Despite some minor misfits and significant item‐trait interaction chi‐square tests ( P < 0.001), the cumulated fit statistics showed that the PPRQ‐17 acceptably satisfies the RMT (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the content of PPRQ seems to corroborate a broader patient perspective; the understanding of staff; theories of PCC; and other similar questionnaires . However, recent Rasch validations of two other similar questionnaires, the Patient Preference for Patient Participation tool (The 4Ps) and Person‐Centered Care in outpatient care in rheumatology (PCCoc/rheum), suggest a unidimensionality for similar subcomponents as the PPRQ. Likewise, previous studies of the PPRQ using CTT revealed high correlations between the subscales, indicating a potential full scale for patient participation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…As suggested, these sections can serve as a basis for dialogues on and plans for health care interventions, in addition to follow‐ups, and/or for evaluation purposes. Considering that patients' preferences for participation may vary with, for example, age, gender, current situation and/or symptoms and their duration, and type of health care contact, the 4Ps has been suggested promising . Yet, its relevance has been primarily established for adults in contact with acute, long‐term, or primary care, but further studies are required to validate its appropriateness, for example, for people with cognitive deficits.…”
Section: Providing For Patient Participationmentioning
confidence: 99%
“…The 4Ps tool comprises four patient-related subscales: 1) Having a dialogue with healthcare staff, 2) sharing knowledge, 3) participating in planning, and 4) managing selfcare. Each subscale comprises three items [15]. The original version of these items was slightly rephrased and translated to Japanese to better t the study objective, and care was taken not to change the item meanings.…”
Section: Instrumentsmentioning
confidence: 99%